Imaging India, imaging Japan : a chronicle of reflections on mutual literature - Sachidanand, Unita; Sakata, Teiji; University of Delhi. Dept. of East Asian Studies; Kokusai Koryu Kikin; Indo-Japan Conference on Mutual Literature (2002 : University of Delhi, Dept. of East Asian Studies) (New Delhi : Manak Publications, 2004)
Contributed articles presented earlier at'Indo-Japan Conference on Mutual Literature' at University of Delhi, Dept. of East Asian Studies in 2002 comparing Indic and Japanese literature
Includes bibliographical references and index
Keywords: Literature, Comparative -- Indic and Japanese -- Congresses; Literature, Comparative -- Japanese and Indic -- Congresses